Reconstruction of a Complex Defect of the Medial Canthal Area - Goulão, João (2018)
Basal cell carcinoma is the most common skin malignancy of the periorbital region. The authors present a clinical case of a large tumor of the medial canthus which excision results in an extensive periorbital defect. Herein, the authors report a “step-by-step” reconstruction by separated aesthetic units using a simple combination of standard flaps, achieving an excellent final result.